2011
DOI: 10.1371/journal.pone.0014781
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Publications in Nephrology and Urology Journals from Chinese Authors in East Asia: A 10-Year Survey of the Literature

Abstract: BackgroundDiseases of the kidneys and genitourinary tract are common health problems that affect people of all ages and demographic backgrounds. In this study, we compared the quantity and quality of nephrological and urological articles published in international journals from the three major regions of China: the mainland (ML), Hong Kong (HK), and Taiwan (TW).MethodsNephrological and urological articles originating from ML, TW, and HK that were published in 61 journals from 1999–2008 were retrieved from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…A double-blind RCT in 73 Chinese patients on hemodialysis in Taiwan showed similar results to previous US and European studies [17]. However, mainland China has more limited medical resources and must serve a larger population of CKD 5D patients across a broader territory than other major regions of China, including Taiwan, which makes comprehensive treatment of these patients more difficult and challenging [21]. Furthermore, there are currently no officially approved phosphorus binders in mainland China.…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…A double-blind RCT in 73 Chinese patients on hemodialysis in Taiwan showed similar results to previous US and European studies [17]. However, mainland China has more limited medical resources and must serve a larger population of CKD 5D patients across a broader territory than other major regions of China, including Taiwan, which makes comprehensive treatment of these patients more difficult and challenging [21]. Furthermore, there are currently no officially approved phosphorus binders in mainland China.…”
Section: Introductionsupporting
confidence: 57%
“…Compared with more developed areas of China, such as Taiwan and Hong Kong, there are limited medical resources in mainland China, and these must serve a large population across a broad territory [21]. In 2002, nearly 1550 per million people (pmp) in Taiwan received regular dialysis treatment; this prevalence was even higher than that in the USA.…”
Section: Discussionmentioning
confidence: 99%
“…And we found that there was a strong negative correlation between MC's average IFs and the annual number of articles. It suggested that respiratory researchers from MC may sacrifice quality for quantity as demonstrated by other reports . It should also be mentioned that IFs are not the only or optimal parameters to identify the quality of articles .…”
Section: Discussionmentioning
confidence: 99%
“…Asian researchers with limited English proficiency may prefer to publish their data in national or regional journals. In fact, although the number of articles published in the fields of urology by researchers from China increased significantly from 1999 to 2008, a substantial amount of their work is still being published in Chinese [22]. Other reasons for Asian under-representation in Western journals might be a bias against researchers from developing countries, with the consequence that the article might be judged with a biased attitude based on the origin of the author [23].…”
Section: Discussionmentioning
confidence: 99%